THE FUNCTIONS OF CONVERSATIONAL IMPLICATURES IN PRINT ADVERTISING - Al Fajri, Muchamad Sholakhuddin (Universitas Pendidikan Indonesia, 2017)
This study aims to examine the use of conversational implicatures(Grice, 1975) in print advertising. It analyses 10 advertisements taken from men and women English and Indonesian Magazines issued in 2016 and 2017. Since advertising is a form of communication between the few (advertisers or company) and the many (public), adverts are supposed to follow the Cooperative Principle and its maxims. However, advertisement designers often do not obey the maxims blatantly or flout the maxims which give rise to an implicature in order to achieve a certain communicative effect. I argue that the application of conversational implicatures in advertisements tends to provide enormous benefits for advertisers or company. The application can perform various functions which eventually make the adverts more effective and persuasive. It could make the adverts more economical or cost-effective, make the ad easy to be remembered, arouse the audience’s curiosity, attract and retain attention and make the advertisers able to avoid responsibility to defend the implied claims.Keywords: Conversational implicature, advertising, cooperative principle, flouting maxims